H∞ control for a networked Markovian jump system subject to data packet loss based on the observer. Issue 1 (16th November 2021) - Wang, Yanfeng; Sun, Xiaoyue; He, Ping; Wu, Zhigang
Abstract: This study researches the H ∞ control issue for a networked Markovian jump system with data packet loss occurring not only in the channel from sensor to controller but also in the channel from controller to actuator via an observer. The mathematical model for the closed‐loop networked Markovian jump system with data packet loss is established. The necessary and sufficient conditions for the closed‐loop system to be stochastically stable are derived. The design approach of the controller and the minimal performance index of the external disturbance suppression are also given in the case that the transition possibilities of the system modes and the data packet loss are both partially unavailable. Finally, two numerical examples are used to illustrate the effectiveness of the proposed method.